Small wind turbines analysis, design, and application - Wood, David (Green energy and technology., 2011)
Small Wind Turbines provides a thorough grounding in analysing, designing, building, and installing a small wind turbine. Small turbines are introduced by emphasising their differences from large ones and nearly all the analysis and design examples refer to small turbines. The accompanying software includes MATLAB programs for power production and starting performance, as well as programs for detailed multi-objective optimisation of blade design. A spreadsheet is also given to help readers apply the simple load model of the IEC standard for small wind turbine safety. Small Wind Turbines represents the distilled outcome of over twenty years experience in fundamental research, design and installation, and field testing of small wind turbines. Small Wind Turbines is a suitable reference for student projects and detailed design studies, and also provides important background material for engineers and others using small wind turbines for remote power and distributed generation applications.